(untitled) (Physical Education, Health and Social Sciences, 2026)
Pakistan’s agricultural sector, historically the backbone of its economy and still accounting for 19–20% of GDP and employing over 40% of the labor force, has undergone significant trade liberalization since the early 1970s, accelerating in the 1990s–2000s through tariff reductions, removal of quantitative restrictions, export subsidies phase-out, and participation in regional trade agreements (SAFTA, China-Pakistan FTA, GSP+ status with the EU). This review employs panel data analysis drawing on dynamic models (GMM, System GMM) and gravity frameworks to assess the impact of trade openness on agricultural export competitiveness, measured via revealed comparative advantage (RCA), export diversification indices, and export growth rates for key commodities (rice, cotton, fruits, vegetables, meat, fisheries). Empirical findings indicate that trade liberalization has yielded mixed outcomes: significant positive effects on export volumes and diversification for rice and certain horticultural products, but persistent competitiveness erosion in cotton textiles due to non-tariff barriers, logistics inefficiencies, high trade costs, and domestic policy distortions (input subsidies, energy shortages). Gravity model estimates highlight the role of improved trade logistics, CPEC infrastructure, and preferential market access in boosting bilateral flows, while time delays and SPS/TBT measures continue to constrain perishable exports. The analysis underscores the need for complementary domestic reforms supply-chain modernization, quality certification, and R&D investment to translate liberalization into sustained competitiveness and inclusive rural growth amid global protectionism and climate vulnerabilities.